Effect of strength training on body composition, strength and aerobic capacity of Brazilians adolescents’ handball players related with peak growth rate. - Mascarenhas, Luis Paulo Gomes (2016)
Objective: During adolescence are expected significant increases in growth rate, strength and body proportions. The purpose of this study was to examine changes in strength, body composition and aerobic capacity after a strength training during different peak growth rate periods in adolescent handball players. Material and method: Twenty-five male adolescents' handball players performed a strength-training program for 8 weeks. The body fat percentage was estimated by Slaughter equation, and the Peak Growth Rate (PGR) defined as: 1 = before peak, 2= within peak; 3= after peak. The repetition maximal test (1 RM) was performance for upper (bench press) and lower-body strength (leg press). Analyze of variance and post-hoc was computed to determine differences between PGR groups, strength and aerobic capacity. Results: No significant changes in body composition were found following after the strength-training program. Upper-body strength increased (A = 26.3%) in the PGR 1 significantly compared to PGR 3 (A = 13.4%) (p < 0.05). No significant changes were found between the PGR groups 1,2 and 3 on aerobic capacity (A = 2.9%, 3.4% and 3.8%, respectively) and lower-body strength raise (A = 11.3%, 19.0% and 15.2%, respectively) after training program in all groups. Conclusions: Changes in body composition were observed between PGR. Aerobic capacity and strength do not differ between limbs at early and average PGR. Increased VO2max, upper and lower-body strength was found in late PGR group in handball players following 8 weeks of strength training.